Media Pembelajaran Interaktif Berbasis Articulate Storyline 3 sebagai Inovasi Pembelajaran IPAS Materi 7 Benua bagi Peserta didik Sekolah Dasar - Sari, Suci Mega Dian; Aziza, Lestari; Nulhakim, Lukman (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the effectiveness of an interactive learning media developed using Articulate Storyline 3 as an innovation for teaching Science and Social Studies (IPAS) on the topic of countries across the seven continents for elementary school students. The research is driven by the need for digital media that can enhance students’ motivation and comprehension in learning global geography concepts that are often abstract and difficult to visualize. A mixed-methods approach with a one-group pretest–posttest design was employed. The participants consisted of 42 sixth-grade students from SDN Cibeber II. Research instruments included learning achievement tests, student response questionnaires, observation sheets, and interviews. The results indicate that the interactive learning media was highly effective in improving students’ learning outcomes. The average score increased from 61.31 to 90.83 after using the media, with an N-Gain value of 0.767, categorized as high. The paired sample t-test confirmed a significant difference between pretest and posttest scores. The questionnaire results showed an average score of 4.78, indicating that students found the media highly engaging, easy to use, and relevant to the material. Observations and interviews further revealed increased motivation, engagement, and conceptual understanding among students. In conclusion, the Articulate Storyline 3–based interactive learning media proved to be effective, feasible, and relevant as an innovative tool for teaching IPAS on the topic of the seven continents. This media can serve as an interactive learning solution aligned with the principles of Kurikulum Merdeka.